Peran Doula Dalam Pemberian Asuhan Kebidanan Pada Masa Kehamilan Dan Persalinan - Yadul Ulya; Siskha Maya Herlina; Regina Pricilia Yunika (JURNAL KESEHATAN TERAPAN, 2026)
Most mothers who experience labor will experience pain and psychological reactions, making them more sensitive to the changes that occur. Appropriate psychological management can be carried out by a birth companion. A birth companion, or doula, can provide emotional support and comfort during labor and can provide information to the mother in labor. The purpose of this study was to analyze the role of doulas in providing midwifery care during pregnancy and childbirth. The method used was a literature review using electronic databases such as Google Scholar, Science Direct, PubMed, and other related sites. The results showed that doula support has significant benefits for the physical and psychological health of mothers in labor. Doulas assist mothers through emotional, physical, informational, and spiritual support, making the labor process more comfortable, safe, and positive. The conclusion is that doula support can be considered part of maternal care that focuses on the holistic needs of the mother and baby.